Daily life physical activity in patients with chronic stage IV sarcoidosis: A multicenter cohort study. Issue 2 (15th January 2019) - Froidure, Sarah; Kyheng, Maeva; Grosbois, Jean Marie; Lhuissier, Francois; Stelianides, Sandrine; Wemeau, Lidwine; Wallaert, Benoit
Abstract: Background and objectives: Little is known about the consequences of chronic sarcoidosis on daily life physical activity (DLPA ). The aim of this prospective study was to measure DLPA in patients with chronic sarcoidosis and to determine its relationship to clinical and functional parameters. Methods: Fifty‐three patients with chronic sarcoidosis and 28 healthy control subjects were enrolled in this multicenter prospective study. Two markers of DLPA (number of steps walked per day [SPD]) and total daily energy expenditure (TEE) were assessed for five consecutive days with a physical activity monitor. Pulmonary function, aerobic capacity (maximal oxygen uptake [VO2 max]), exercise capacity (6‐min walk test [6MWT]), and quality of life (self‐reported questionnaires) were also evaluated. Comparisons of DLPA parameters between the two groups were performed using an analysis of covariance adjusted for age, sex, and body mass index (BMI). Relationships between DLPA parameters and patient characteristics were assessed in multivariable linear regression models. Results: Patients with sarcoidosis walked significantly fewer SPD than did the control subjects (6395 ± 4119 and 11 817 ± 3600, respectively; P  < 0.001 after adjustment for age, BMI, and sex). TEE was not significantly different between patients with sarcoidosis and healthy controls (median [interquartile range]: 2369 [2004‐2827] and 2387 [2319‐2876] kcal/day, respectively, P  = 0.054 adjusted for age, BMI, and sex). SPD showed significant positive correlations with 6MWT distance (Pearson's correlation, r  = 0.32, 95% confidence intervals [95%CI] = 0.06, 0.55; P  = 0.019), VO2 max ( r  = 0.44, 95%CI = 0.17, 0.65; P  = 0.002), and Visual Simplified Respiratory Questionnaire score ( r  = 0.44, 95%CI = 0.19, 0.64; P  = 0.001), and a significant negative correlation with modified Medical Research Council questionnaire score ( r  = −0.38, 95%CI = −0.60, −0.10; P  = 0.009). TEE was significantly correlated with BMI ( r  = 0.38, 95%CI = 0.13, 0.59; P  = 0.004), forced expiratory volume in 1 second ( r  = 0.55, 95%CI = 0.33, 0.71; P  < 0.001), total lung capacity ( r  = 0.44, 95%CI = 0.18, 0.64; P  = 0.001), and forced vital capacity ( r  = 0.56, 95%CI = 0.34, 0.72; P  < 0.001). In multivariable analysis, SPD remained associated only with VO2 max. Conclusion: Patients with chronic sarcoidosis appear to have reduced DLPA mainly because of compromised VO2 max.